ANALISIS KEPUTUSAN KONSUMEN TERHADAP PEMBELIAN JERUK KINTAMANI DI KOTA DENPASAR - Yosafat, Jefri; Mulyani, Sri; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): JuniDO - 10.24843/JRMA.2019.v07.i02.p14, 2019)
The objectives of  this research  were to analyze the  factor which influence of consumer decision to buy Kintamani orange. This research  were  using a factor analyze by using Microsoft Excel and SPSS 25.0 .  The data obtained from the questionnaire which spread to the consumer of Kintamani orange.  The results show that there are 24 variable divided into 5 factor which influence of consumer decision to buy Kintamani orange. The five factors are characteristic of orange corresponding to the price and competitor, benefit and quality corresponding to the price and product category, the origin of orange corresponding to benefit and consumer perception, the category of orange consumen, and the orange resistance. The factor that the most influence of consumer decision to buy Kintamani orange is taste (The taste of Kintamani orange is a mixture of sweet and sour) .  The research  proposed are  to an information to people about Kintamani orange, and an information to the orange farmer and seller of Kintamani orange about the the factor and the main factor that influence consumer to buy Kintamani orange and the special benefit is as a reference knowledge to academic student. Keywords :  kintamani orange, factor analyze, consumer decision, strategy proposed